Pemanfaatan Beras (Oryza sativa) sebagai Tumbuhan Komoditi Kabupaten Karawang untuk Pengobatan Tradisional: Sebuah Tinjauan Literatur - Siska Bela Safitri; Dia Septiani (Poltekkes Kemenkes Padang, 2024)
Karawang Regency is a producer of 1,485,298 tons of harvested dry grain per year. Rice is used as the main staple food that has medicinal benefits due to the content of secondary metabolites such as flavonoids, tannins, phenolic acids, and terpenoid compounds. Methods This study used PUBMED and Scienedirect scientific search engines with the keywords (((Oryza sativa)) AND ((traditional medication))), (Oryza sativa) AND (commodity crops) and Oryza sativa for traditional medication. For literature selection, the PRISMA method was used by searching the literature on Pubmed and ScienDirect, 95 journals were obtained, then eligibility criteria were determined based on the inclusion and exclusion criteria so that 2 journals were obtained to be extracted. The results of the literature study obtained 2 journals used for data extraction in the literature review, which explained the content of secondary metabolites, preparations used and their efficacy for treatment. The conclusion is rice has medicinal properties due to the content of phenolic and flavonoid secondary metabolites that support antioxidant activity for therapy in degenerative diseases and melanoma. Recommended So that research on rice from Kawarang Regency must be developed because it is very potential and this research literature is still difficult to find.